2010
DOI: 10.1086/652408
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of HIV Acquisition among Kenyan Men with Human Papillomavirus Infection

Abstract: Background Few data are available concerning the effect of human papillomavirus (HPV) infection on HIV acquisition. Methods HIV-seronegative, sexually active 18-24 year-old Kenyan men within a randomized trial of male circumcision provided penile exfoliated cells from two anatomical sites (glans/coronal sulcus, and shaft) at baseline. The GP5+/6+ PCR assay ascertained a wide range of HPV DNA types at the baseline visit. Risk of HIV infection [95% confidence interval (CI)] was estimated using Kaplan-Meier met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 19 publications
3
71
0
1
Order By: Relevance
“…This is highly significant when considered with the previously discussed findings that genital HPV infections can predispose to increased risk of HIV transmission in both men and women [29,30].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This is highly significant when considered with the previously discussed findings that genital HPV infections can predispose to increased risk of HIV transmission in both men and women [29,30].…”
Section: Discussionmentioning
confidence: 72%
“…With current pricing strategies, anti-HPV vaccines are not an option in such settings, and as previously discussed, they will most likely have reduced efficacy in HIV-positive women. Furthermore, in view of the observation that infection with HPV can enhance the sexual transmission of HIV in both men and women [29,30], this clearly indicates that a simple, non-surgical treatment for HPV-related precancerous lesions may not only reduce the burden of cervical cancer but may also reduce the chances of HIV transmission.…”
Section: Discussionmentioning
confidence: 94%
“…[9] Although data on anogenital HPV DNA prevalence in men in SSA are also limited, [3] overall reported prevalences in men are high, ranging from 19% to 78%. [10][11][12][13][14][15] In most, but not all studies, the most prevalent type was HPV-16. [15] The observed heterogeneity in estimates can be attributed to differences in age distribution, sexual behaviour and HIV prevalence within the different populations.…”
Section: Burden Of Infection In Ssamentioning
confidence: 99%
“…Lack of circumcision and HIV infection have been identified as risk factors for AGWs in men. [12] Importantly, HIVpositive men with AGWs may also be at risk for infection with HR-HPV. In a small study in Johannesburg among HIV-positive men with penile warts, 85% were found to have HR-HPV as well.…”
Section: Reviewmentioning
confidence: 99%
“…An HPV subset is also clearly implicated in the development of human anal, vaginal, vulvar, penile, and oropharyngeal malignancies (2,(9)(10)(11). Moreover, anal HPV infections, especially highrisk types, were suggested previously to be independently associated with HIV acquisition (12).…”
mentioning
confidence: 99%